If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27c + 5 + -25c = 49 Reorder the terms: 5 + 27c + -25c = 49 Combine like terms: 27c + -25c = 2c 5 + 2c = 49 Solving 5 + 2c = 49 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2c = 49 + -5 Combine like terms: 5 + -5 = 0 0 + 2c = 49 + -5 2c = 49 + -5 Combine like terms: 49 + -5 = 44 2c = 44 Divide each side by '2'. c = 22 Simplifying c = 22
| 9a+5a+7a+8a= | | 5(4x-2)=2(3+6x) | | 15x-2x=-7x | | 42x-210=27x | | 3+10a-8=15 | | 6x-9+2x=5+8x-13 | | 2+x+y=x+5 | | 2x-2+2y=2+x+y | | 5r^2-19r-4= | | -3p+2+4p=-5 | | +65+(x-5)=180 | | x^4+15x-30= | | 7+20x=4(5x+3) | | 4y+9=3y-3 | | +65+(x-5)=60 | | 1.01*0.231= | | 6=-0.2r | | 5x+6=2x+13 | | 3x+2=3+x+3 | | 7y-14-4y+9=0 | | T=hp+b | | 3x+2=3+x-3 | | 3x+2=3+x-y | | 4x+7+5x=6x-11 | | 12=3h+4-h | | 3x-2=18x+8 | | Y-2=7(x+1) | | -1+6x=65 | | 6=0.9 | | 3b+4=30 | | -7+2x+x+10=8 | | -5x+8=-52 |